(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, educational platforms have been studied and analyzed, including the adaptive implementation of the educational process, which is possible through the use of SMART educational technologies, the implementation of the SMART educational paradigm is educational and is aimed at shaping the educational process, as well as opinions and comments on SMART which makes it possible to use the global information society to meet educational needs and interests.